CÓDIGOS IDENTIFICADORES DA REPRESENTAÇÃO DA ORALIDADE EM MAU TEMPO NO CANAL - Blayer, Irene Maria Ferreira (Organon, 2007)
The most impressive trait of Vitorino Nemésio’s oral style is the unifying linguistic indicators exhibited in the direct speech of his characters. In this literary attempt to mark the speaker’s dialectal codes of speech, Nemésio seeks to construct a personality that stands apart, linguistically, from others in the text. In this essay, the literary representation of dialect in the discourse of one of the characters in Mau Tempo no Canal1 provides a background upon which the marked linguistic registers will be traced against existing linguistic data to form an expository analysis of the speech. The question is whether this oral fictional speech represents a truthful marker of Azorean linguistic identity.